Sample preparative procedure for Pseudomonas aeruginosa observation under scanning electron microscope - Nguyen, Ngoc Hoa Binh; Pham, Thi Thuy Vy; Huynh, Thuc Quyen; Nguyen, Thi Hiep; Nguyen, Thi Thu Hoai (Vietnam Journal of Biotechnology, 2022)
Scanning electron microscope (SEM) is a popular tool used for observing bacteria surface and morphology. Using Pseudomonas aeruginosa as a model, this work aimed to show a SEM preparative procedure that is simple and economical but does not result in considerable data loss. This was accomplished via testing fixing ability of 10% formalin versus 2.5% glutaraldehyde, efficiency of air drying versus t-butyl alcohol drying method. Following that, polypropylene, dialysis tubing and agar were also assessed for their ability to serve as a supporting material for cell adhesion in preparing sample for SEM. Consequently, obtained data showed that the procedure using 24-hour 10% formalin fixation and t-butyl alcohol drying preserved well bacterial morphology. With this procedure, little cell or membrane damage was seen while extracellular structures were clearly observed. Furthermore, when this procedure was applied with different types of substrates including polypropylene, dialysis tubing, and agar, it showed that sample fixed on polypropylene maintained well extracellular structures meanwhile sample fixed on agar presented well bacterial morphology. In conclusion, our data suggested that coating samples on polypropylene, followed by 24-hour 10% formalin fixation and t-butyl alcohol drying was appropriate for observing bacteria under SEM.